Big Bird can share - Anastasio, Dina.; Leigh, Tom; Children$1 (Bs Television Workshop.s ([New York] : Western Pub. Co. in conjunction with Children$1 (Bs Television Workshop,s, 1985)
Big Bird shares his new pail and shovel with his friends with amazing results.
"Featuring Jim Henson$1 (Bs Sesame Street Muppets."s
"A Sesame Street/Golden Press book."
"A Golden book"--Cover.
Keywords: Sharing -- Fiction; Puppets -- Fiction